Design-Based Research – ein Ansatz empirischer Forschung und seine Potentiale für die Geographiedidaktik - Feulner, Barbara; Ohl, Ulrike; Hörmann, Isabel (Journal of Geography Education, 2015)
The research methodology design-based research (DBR) combines didactic theory, empirical research, and educational practice. Teaching concepts are developed in accordance with both theoretical and empirical research findings; through multiple iterations, these concepts are assessed in practice, modified according to the findings of the accompanying research, and finally tested again in practice. The purpose of this approach is to contribute both to the development of didactic theory and to improve educational practice. DBR facilitates the transfer of research results into teaching practice, and is intended to reinforce the collaboration between science and practice through, among other things, close cooperation between scientists and practitioners. Until now, DBR has found little application in geographical education research. To examine the potential of this approach more closely, this paper presents the theoretical backgrounds and methods of DBR projects, specifies the types of scientific output, and discusses the methodological challenges for research that DBR entails. An illustration of this methodology is based on two current DBR research projects in the field of geography education. One study on location-based mobile learning examines so-called Geogames with regard to their applicability and effectiveness. The second survey deals with the theory-driven development of a teaching and learning environment which demonstrates the production, destruction, and the various effects of ozone.